29.8k views
3 votes
5(2c-3) = 3(3c - 5)

Answer Choices:
No solution
c = -15
c = 0
Infinitely many solutions​

User FileX
by
4.5k points

2 Answers

3 votes

Answer:

C=0

Explanation:

Hope it helps.

User Mankowitz
by
5.4k points
5 votes

Answer: C=0

Explanation:

expand
5\left(2c-3\right) :
10c-15

expand
3\left(3c\:-\:5\right) :
9c-15


10c-15=9c-15

add 15 on both sides


10c-15+15=9c-15+15

simplify


10c=9c


\mathrm{Subtract\:}9c\mathrm{\:from\:both\:sides}


10c-9c=9c-9c

simplify


c=0\\

User Kadiatu
by
5.1k points